2000
DOI: 10.1021/jo991625m
|View full text |Cite
|
Sign up to set email alerts
|

Novel tert-Butyl Migration in Copper-Mediated Phenol Ortho-Oxygenation Implicates a Mechanism Involving Conversion of a 6-Hydroperoxy-2,4-cyclohexadienone Directly to an o-Quinone

Abstract: Copper mediated ortho-oxygenation of phenolates may proceed through the generation of a 6-peroxy-2,4-cyclohexadienone intermediate. To test this theory, we studied the fate of sodium 4-carbethoxy-2, 6-di-tert-butylphenolate, where the ortho-oxygenation sites are blocked by tert-butyl groups. Using the Cu(I) complex of N, N-bis(2-(N-methylbenzimidazol-2-yl)ethyl)benzylamine, isolation of the major oxygenated product and characterization by single-crystal X-ray crystallography and NMR spectroscopy revealed it to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…As a final comment it can be noted that the structure in Fig. 6 is very similar to some previous suggestions for the mechanism of tyrosinase [2,18,19].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As a final comment it can be noted that the structure in Fig. 6 is very similar to some previous suggestions for the mechanism of tyrosinase [2,18,19].…”
Section: Resultssupporting
confidence: 84%
“…For example, it has been shown that a l-g 2 :g 2 -peroxide Cu 2 (II,II) dimer can be reversibly converted by O-O bond cleavage to a bis-loxo Cu 2 (III,III) dimer under very mild conditions using the tridentate triazacyclononane ligand on each copper center. The O-O bond cleavage mechanisms (b) and (c) are supported by other experiments [1,2,18,19].…”
Section: Introductionsupporting
confidence: 78%
“…Substituted biphenols, diphenoquinone and para-quinone have been reported as oxidation products of hindered phenols using copper(I) and copper(II) complexes [6][7][8][9]. A mechanism involving tert-butyl migration and a 6-hydroperoxy-2,4-cyclohexadienone intermediate is also postulated, involving a copper(I) mediated oxidation [10]. A recent study at low temperature employs a cupric-superoxo complex for the study of oxidation of substituted di-tertbutylphenols and proposes a cupric superoxo-phenoxyl radical as intermediate forming 2,6-di-tert-butyl-1,4-benzoquinone [11].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the substrate present in tyrosinase and catechol oxidase, but not in hemocyanin, could also play a role in the dioxygen activation. Inspired by the presence of these complexes in enzymes, important work on synthetic copper dimer model compounds has been made mainly by the research groups of Kitajima [8], Karlin [9,10], Tolman [11,12], Stack [13], Sayre [14,15], and Casella [16]. For example, Tolman and co-workers [11,12] found that a l-g 2 :g 2 -peroxide Cu 2 (II,II) dimer can be reversibly converted by O-O bond cleavage to a bisl-oxo Cu 2 (III,III) dimer (L=triazacyclononane), under very mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For other reasons, the formation of the bis-l-oxo Cu 2 (III,III) state has been considered unlikely in the enzymes and other mechanisms for activating dioxygen has therefore been suggested for tyrosinase, such as a simultaneous activation of the O-O bond and substrate (i.e. the peroxo unit attacks the arene ring directly) [2,14,15].…”
Section: Introductionmentioning
confidence: 99%